(untitled) (Research, Society and Development, 2023)
According to the World Health Organization, "cardiovascular disease is the leading cause of death globally, accounting for 30% of global deaths." These deaths are related to atherosclerosis, which is the accumulation of cholesterol in the blood, leading to the buildup of fat in the arteries, ultimately resulting in blockages. Consequently, many individuals seek treatments, including nutritional strategies, to improve, or even prevent, undesirable changes in blood lipid levels and inflammatory markers. Thus, this study aimed to analyze the differences in the impacts that saturated and unsaturated fatty acids can have on cardiovascular health and hematologic test lipid profile. Through the review of scientific articles and guidelines from various countries, it was possible to observe that replacing saturated fats with monounsaturated and polyunsaturated lipids leads to a reduction in inflammatory markers, improves the treatment of dyslipidemias, and, most importantly, decreases cardiovascular risks.